The history of origin and development of cable television Republic of Korea. - Alimbayeva, Zhanna N. (Journal of Oriental Studies, 2016)
The television is the basic direction in distributions of a masscult culture. The main feature of development of a television epoch is distributions of satellite television. The satellite television of South Korea is a basic way of distribution of a masscult culture.